Microfracture for Ulnar Impaction Syndrome: Surgical Technique and Outcomes with Minimum 2-Year Follow-up - Kaufman, David; Etcheson, Jennifer; Yao, Jeffrey (Journal of Wrist Surgery, 2017)
Purpose The purpose of this study is to assess functional and patient-reported outcomes after lunate microfracture for management of lunate chondral lesions in the setting of ulnar impaction syndrome.Methods This was a retrospective review of all patients undergoing wrist arthroscopy for triangular fibrocartilage complex pathology by one surgeon from 2007 until 2010. Disabilities of the arm, shoulder, and hand (DASH) scores were assessed preoperatively and at minimum 2-year follow-up. Patient-rated wrist evaluation and bilateral wrist range of motion, grip strength, and key pinch strength were assessed at final follow-up.Results A total of 22 patients underwent microfracture of the carpus during the study period, of which 7 met all inclusion and exclusion criteria. Mean DASH scores improved significantly (p < 0.001), from 58.3 (standard deviation: 13.5) before the procedure to 15.1 (standard deviation: 8.6) at minimum 2-year follow-up. Operative wrist pronation and supination showed equivalence with the contralateral wrist at final follow-up (p < 0.05, E = 15 degrees, standard deviation pronation: 3.25, supination: 3.49).Discussion This study suggests that lunate microfracture may be a useful technique for treating articular defects of the lunate in the setting of ulnar impaction syndrome.Type of Study/Level of Evidence Therapeutic, level IV.
Keywords: microfracture; ulnar impaction syndrome; ulnocarpal abutment syndrome; ulnocarpal arthritis; wrist arthroscopy